EFL Students’ Perceptions on Using Short Stories with Videos from LearnEnglishKids as Autonomous Learning Activity - Kamar, Fauziah; Marlina, Leni (Journal of English Language Teaching, 2024)
This study explores EFL students' perceptions of using short stories with videos from LearnEnglishKids as part of their autonomous learning activities in a listening class. Employing a descriptive research approach with a quantitative methodology, the study focused on students from the Basic Listening class in the English Department at FBS, Universitas Negeri Padang (UNP). Data were gathered from 22 students through a questionnaire containing 25 closed statements rated on a 4-point Likert scale and interviews that concentrated on six key questions regarding students' perceptions of using short stories with videos from LearnEnglishKids as an autonomous learning activity. The findings suggest that most students enjoy and appreciate watching these short stories with videos, perceiving them as highly beneficial for enhancing comprehension, engaging both visual and auditory senses, and increasing overall enjoyment in learning English, which in turn significantly improves their listening skills. The average perception score of 3.23 out of 4 reflects a positive impact. The research suggests that incorporating digital resources like short stories with videos from LearnEnglishKids into autonomous learning activities in listening classes can be highly effective.